An ACTH-secreting tumour hidden in a congenitally hypoplastic left lung. (16th May 2022) - Chen, Xueyu; Zhang, Yajie; Lin, Jules; Li, Hecheng
Abstract: Ectopic adrenocorticotrophic hormone (ACTH) syndrome has historically been a therapeutic challenge because of the difficulty localizing occult ACTH-secreting tumours. Here, we report a case of a 67-year-old woman with ectopic ACTH syndrome and had an ACTH-secreting tumour hidden within a congenitally hypoplastic left lung. A satisfactory therapeutic outcome was obtained after left pneumonectomy was performed on patient in this case. Abstract : Ectopic adrenocorticotrophic hormone (ACTH) syndrome (EAS) is due to the specific secretion of biologically active ACTH by tumour tissues located outside the pituitary, which stimulates renal epithelial hyperplasia to produce excessive cortisol leading to Cushing's syndrome [1].